The Determinants of Board Compensations: Evidence from Indonesia - SALIM DARMADI (The Indonesian Journal of Accounting Research, 2013)
This paper examines the determinants of board compensation in a developing economy that adopts a twotier board structure system. Corporate governance structure, firm-specific characteristics, and firm performance are hypothesized as significant determinants. The sample consists of 442 firm-year observations, comprising 255 listed firms on the Indonesian Stock Exchange (IDX) in the financial years 2006 and 2007. I provide empirical evidence that profitability, firm size, and the number of board members are positively associated with the compensation level. Family-controlled firms are found to spend a higher proportion of their financial resources on compensating their board members, leading to a higher probability of agency problems in such firms. Further, this study investigates pay-performance sensitivity and reveals that changes in firm value are positively associated with changes in board compensation.